Princess & Fairy, or, The Wonders of Nature - Martyn, Lily (W. & R. Chambers Ltd., 1899)
Through the personas of a princess and a fairy, this volume explains different so-called "wonders of nature" to young readers, including insects, several varieties of flowers, snow crystals, metals, and clouds. The volume includes sixty-eight illustrations to augment the information provided.
Keywords: Natural history; Children's literature; Science; Science--Study and teaching